2018
DOI: 10.4103/ijdr.ijdr_475_17
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and fluorosis among children in Lebanon

Abstract: Survey results confirm the need to implement nationwide dental caries prevention measures. Since water fluoridation is not feasible, salt fluoridation would be the alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…This can also explain the higher value of filled teeth on FSFP. A study of 2018, in Beirut, Lebanon, in a sample of 1433 children aged 6-8, without fluoridated water showed caries indexes of DMFT and dmft of 0.60 and 5.15, values similar to those found in our study (Doumit & Doughan, 2018). The Community with no fluoridated water program (CNF) had dmft value of 3.82 and DMFT of 1.48, results which are lower and slightly higher, respectively to similar data on previous studies with no fluoride added on tap water (Urbina et al; Yévenes et al).…”
Section: Discussionsupporting
confidence: 89%
“…This can also explain the higher value of filled teeth on FSFP. A study of 2018, in Beirut, Lebanon, in a sample of 1433 children aged 6-8, without fluoridated water showed caries indexes of DMFT and dmft of 0.60 and 5.15, values similar to those found in our study (Doumit & Doughan, 2018). The Community with no fluoridated water program (CNF) had dmft value of 3.82 and DMFT of 1.48, results which are lower and slightly higher, respectively to similar data on previous studies with no fluoride added on tap water (Urbina et al; Yévenes et al).…”
Section: Discussionsupporting
confidence: 89%
“…The present study revealed lower caries severity (3.90 in Kraśnik and 4.02 in Chervonograd) than the index value of 5.18 calculated by Smolar (47). Similarly high values of the D3MFT number were obtained in Lebanon: 5.44 (48) and Lithuania: 5.6 (33). The statistical analysis of the data obtained in the present study showed a higher value of the SIC index in the group from Chervonograd, i.e.…”
Section: Clinical Examinationssupporting
confidence: 81%
“…Approximately three‐quarters of Syrian children experience high ECC (dmft = 4.25), and this was significantly associated with bottle‐feeding during infancy and toddlerhood. In Lebanon, 88% of children with deciduous teeth suffered from dental caries, and 94.4% of dental caries was not treated. Poor toothbrushing routines and limited access to dental care services in addition to high consumption of sugar and lack of free fluoride toothpaste or fluoride applications lead to plaque accumulation on the teeth and root surfaces.…”
Section: Introductionmentioning
confidence: 99%